Keeping Faith - Daniels, Lucy (New York Hyperion, 2002)
When her family's riding school is forced to close, Josie Grace tries to find a caring owner for her elderly horse, Faith.
"Volo."
Originally published in England by Hodder Children's Books under the series title "Perfect ponies."
Keywords: Horses -- England -- Juvenile fiction; Teenage girls -- England -- Juvenile fiction; Riding schools -- England -- Juvenile fiction; Horses -- England -- Fiction; Teenage girls -- England -- Fiction; Riding schools -- England -- Fiction